Analysis of Sanitation and Diarrhea Factors with The Incidence of Stunting in Indonesia: A Meta-Analysis Study - Dwi Wahyuni, Sumarti; Husnina, Zida; Sulistyorini, Lilis; Azizah, R. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Stunting is a significant public health problem for toddlers in developing countries. The prevalence of stunting in Indonesia in 2018 was 30.8%. Referring to the target of the National Medium-Term Development Plan (RPJMN) in 2019, the stunting rate of 28% has yet to be achieved. Determinants of stunting include direct and indirect factors. Direct factors are nutritional intake and infectious diseases. Indirect factors are food adequacy, parenting, sanitation, clean water, and essential health services. This study aims to summarize scientific evidence related to the relationship between sanitation and diarrhea factors and stunting in toddlers. This study uses meta-analysis, and article sources come from Google Scholar, Science Direct, and PubMed. Based on the inclusion requirements of the writing, namely informing about sanitation and diarrhea with stunting cases in toddlers, observational research designs, and publication years 2018–2022, 15 articles were obtained. Based on the meta-analysis results, sanitation (clean water) was the highest risk factor, with a pooled value of PR = 4.437 (95% CI 0.67–2.30). The lowest risk factor was latrines, with a pooled PR = 2.459 (95% CI -0.04–1.39). Analysis of diarrhea variables with pooled value PR = 1,404 (95% CI 0.12–0.56). It was concluded that the most significant risk was the clean water factor. Essential factors to control stunting risk are preparing the availability of clean water, advocating for local governments to take a leading role in providing clean water to areas in need, initiating behavior change, and increasing awareness about stunting risks as part of prevention programs.